Überarbeitung des BVWP. Entwicklung und Nutzung des Projektinformationssystems PRINS zur Entscheidungsvorbereitung bei der Aufstellung des Bundesverkehrswegeplans 2003. - Graichen, Hans-Michael; Vosdellen, Lothar (Deutscher Verkehrs-Verlag, 2005)
Zur Aufstellung des neuen Bundesverkehrswegeplans (BVWP) wurden für Projekte der Verkehrsträger - Bundesschienenwege, Bundesfernstraßen und Bundeswasserstraßen - von Verwaltungen und Gutachtern umfangreiche Beurteilungsgrundlagen erarbeitet. Mittels eines Datenverarbeitungssystems sollten sämtliche Projektinformationen erfasst, verwaltet, für die Entscheidungsfindung aufbereitet und schnell verfügbar gemacht werden. Der Beitrag gibt einen zusammenfassenden Überblick über den Gesamtumfang der Arbeiten zum Projektinformationssystem PRINS vom Systemaufbau über den Betrieb bis hin zu den Ergebnisdarstellungen. difu

During the compilation of the current BVWP (Federal Highway Plan), all the available documents, details about the project and related statements are to be officially recorded and evaluated by making use of the latest forms of information technology. In order to facilitate the process of decision making, it has been requested to produce ad hoc printouts featuring an overview of the project, its evaluation and relevant statistics. To achieve all this, the use of the ORACLE data bank has led to the creation of a data administration system that offers a high degree of flexibility and data files' security while being user friendly and incorporating the latest technological achievements. This system has made it possible to record, analyze and review all the information needed for making decisions about those projects, which involve the federal rail system, trunk road system and inland waterways, thus supporting the decision making process and documenting the ongoing progress. Since preparing the BVWP report for 2003, the information system PRINS has proved a suitable tool that can provide relevant data during the evaluation process. By regularly updating, and perfecting, the data at hand, this system can adequately meet any future requirements. difu
Keywords: Verkehrsweg; Verkehr; Verkehrsentwicklung; Verkehrswegeplanung; Schienenverkehr; Straßenverkehr; Bundesfernstraßenplanung; Binnenschiffsverkehr; Verkehrsinfrastruktur; Bundesverkehrswegeplan; Informationssystem; EDV-Einsatz; Projektdarstellung; Verkehrsträger; Verkehrsangebot